Haplogenome analysis and genetic dissection of growth and wood property traits in Eucalyptus urophylla x E. grandis hybrids - Myburg, Alexander Andrew (University of Pretoria, 2024)
Thesis (PhD (Genetics))--University of Pretoria, 2024.